X chromosome gene methylation in peripheral lymphocytes from monozygotic twins discordant for scleroderma - Selmi, C (Blackwell Science Inc, 2012)
Scleroderma (SSc) is a rare connective tissue disease characterized by fibrosis, microvasculopathy and autoimmune features. The role of genetics is limited in SSc, as suggested by similar concordance rates in monozygotic and dizygotic twin pairs, while environmental factors may act through epigenetic changes, as demonstrated for specific genes. Further, sex chromosome changes have been reported in SSc and may explain the female preponderance. In the present study we compared the methylation profile of all X chromosome genes in peripheral blood mononuclear cells from monozygotic twins discordant (n = 7) and concordant (n = 1) for SSc. Methylated DNA immunoprecipitations from each discordant twin pair were hybridized to a custom-designed array included 998 sites encompassing promoters of all X chromosome genes and randomly chosen autosomal genes. Biostatistical tools identified sites with an elevated probability to be consistently hypermethylated (n = 18) or hypomethylated (n = 25) in affected twins. Identified genes include transcription factors (ARX, HSFX1, ZBED1, ZNF41) and surface antigens (IL1RAPL2, PGRMC1), and pathway analysis suggests their involvement in cell proliferation (PGK1, SMS, UTP14A, SSR4), apoptosis (MTM1), inflammation (ARAF) and oxidative stress (ENOX2). In conclusion, we propose that X chromosome genes with different methylation profiles in monozygotic twin pairs may constitute candidates for SSc susceptibility.